Pengaruh Penggunaan Teknologi Dan Komunikasi Virtual Terhadap Produktivitas Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Kesehatan Kota Padang - Muhammad Fajrin; Desi Permata Sari; Hilda Mary (Jurnal Ekonomi dan Bisnis Digital, 2026)
Employee productivity is a crucial factor in organizational success. However, employee productivity at the Padang City Health Office still faces challenges due to the suboptimal use of technology and virtual communication in supporting work execution. This study aims to analyze the impact of technology usage and virtual communication on employee productivity, with job satisfaction serving as an intervening variable, at the Padang City Health Office. The study employs a quantitative method with an associative approach. The research population consists of 55 employees, selected using a non-probability sampling technique. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with the SmartPLS 4 application. The results indicate that technology usage has a positive and significant effect on job satisfaction and employee productivity. Conversely, virtual communication was found to have no effect. significant impact on employee job satisfaction and productivity. Job satisfaction has a positive and significant effect on employee productivity. Furthermore, job satisfaction mediates the impact of technology usage on employee productivity but fails to mediate the impact of virtual communication on employee productivity. This research is expected to provide valuable insights for the Padang City Health Office.